2009
DOI: 10.1111/j.1464-410x.2009.08649.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiomyolipomata: challenges, solutions, and future prospects based on over 100 cases treated

Abstract: Study Type – Therapy (case series) Level of Evidence 4 OBJECTIVE To examine the presentation, management and outcomes of patients with renal angiomyolipoma (AML) over a period of 10 years, at St George’s Hospital, London, UK. PATIENTS AND METHODS We assessed retrospectively 102 patients (median follow‐up 4 years) at our centre; 70 had tuberous sclerosis complex (TSC; median tumour size 3.5 cm) and the other 32 were sporadic (median tumour size 1.2 cm). Data were gathered from several sources, including radiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
98
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(107 citation statements)
references
References 25 publications
4
98
0
5
Order By: Relevance
“…The first is more frequent in AMLs, whereas hematuria is associated with TSC in these patients. However, recent reports on the frequencies of such symptoms have been indicative of a general reduction in these clinical manifestations; for instance, the rate of pain was 37% to 41%, which declined to 35% over a decade in the 2010s (9,10). The characteristic feature of renal AML is thick-walled blood vessels, which do not have normal elastin and are prone to rupture (11).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The first is more frequent in AMLs, whereas hematuria is associated with TSC in these patients. However, recent reports on the frequencies of such symptoms have been indicative of a general reduction in these clinical manifestations; for instance, the rate of pain was 37% to 41%, which declined to 35% over a decade in the 2010s (9,10). The characteristic feature of renal AML is thick-walled blood vessels, which do not have normal elastin and are prone to rupture (11).…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, another study revealed that tumors with serial changes in volumes were associated with higher probability of hemorrhagic lesions (13). As for TSC patients, their tumors tend to be multifocal, bilateral, and larger when compared to those tumors in sporadic AMLs (10). AML in pregnant women often remains undetectable with the equivocal risk of rupture (14).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For benign AMLS, renal preserving treatment such as selective angioembolization and nephron-sparing surgery are preferred [37]. Thermo-ablation as RFA has also been reported to be a promising treatment for AMLs also in patients with a solitary kidney [38,39]. Considering the several theoretical advantages of microwave with respect to radiofrequencies, Zhi-yu et al [37] have proposed a study to evaluate the safety and efficacy of MWA for the treatment of sporadic renal AML.…”
Section: Percutaneous Mwa Of Renal Tumors: Clinical Seriesmentioning
confidence: 99%